2021
DOI: 10.1186/s12913-021-06426-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying homeless population needs in the Emergency Department using Community-Based Participatory Research

Abstract: Background Annually 1.5 million Americans face housing insecurity, and compared to their domiciled counterparts are three times more likely to utilize the Emergency Department (ED). Community Based Participatory Research (CBPR) methods have been employed in underserved populations, but use in the ED has been limited. We employed CBPR in an urban American hospital with a primary goal of improved linkage to care, reduced ED recidivism, and improved homeless health care. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…These results complement the existing body of literature on the experience of homeless individuals accessing health care (Franco et al, 2021;Martins, 2008;O'Carroll & Wainwright, 2019;Omerov et al, 2020;Ramsay et al, 2019). With homeless service programs prioritizing housing first (Tsai et al, 2017), homeless individuals in this study experienced access to health care as transactional.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These results complement the existing body of literature on the experience of homeless individuals accessing health care (Franco et al, 2021;Martins, 2008;O'Carroll & Wainwright, 2019;Omerov et al, 2020;Ramsay et al, 2019). With homeless service programs prioritizing housing first (Tsai et al, 2017), homeless individuals in this study experienced access to health care as transactional.…”
Section: Discussionsupporting
confidence: 73%
“…The third theme, Care Coordination Resources Are Inadequate, reflects the SDOH that negatively affect the health of homeless individuals (Doran et al, 2016;Franco et al, 2021). SDOH complicate traditional approaches to care planning; thus, they can be insufficient to meet their needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledging that emergency departments are extremely busy, and the tempo of practice means that tackling the often-complex issues facing people experiencing homelessness can be highly challenging. People experiencing homelessness have reported that they leave the emergency department having had very few of their needs met [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is debate as to the role that emergency departments can have in interrupting the cycle of homelessness. Proponents argue that because most people experiencing homelessness access emergency department care, their attendance is an opportunity not to be missed to link this vulnerable population with healthcare and other services [ 23 , 24 ]. Yet, evidence suggests that some emergency departments are under resourced to meet the myriad of health and social needs of people experiencing homelessness [ 25 ].…”
Section: Introductionmentioning
confidence: 99%